Detecting to the beat of your own drum: the phase of low-delta oscillations leads a subject-specific mix of higher frequencies in the determination of visual-target detection - Fiebelkorn, I.; Snyder, A.; Mercier, M.; Butler, J.; Molholm, S.; Foxe, J. (Journal of vision (Charlottesville, Va.), 2012)
Abstract only